Fisheries and marine ecosystems in Sabah [Malaysia] - Brusing, E.R. (Fisheries Dept., Kota Kinabalu, Sabah (Malaysia) Likas Fisheries Research Center) (Jabatan Perikanan Malaysia, 2013)
The marine fisheries in Sabah and its relationship with the marine ecosystems are discussed. The paper describes a few aspects of the fisheries industry in Sabah, main marine ecosystems related to the fishery and their conservation. Finally, this paper discusses the problem of red tide blooms and their preventive measures in the state.